Lingkungan Kerja Fisik, Kepemimpinan, Motivasi Kerja, dan Kompensasi dalam Mempengaruhi Kinerja Karyawan Bagian Pemasaran pada PT Mitra Bisnis Keluarga Ventura Banyumas - P. Edi Sumantri; Ari Astuti; Endang Sri Wahyuningsih (FEB UNWIKU PURWOKERTO, 2022)
This study aims to determine the effect of the physical work environment, leadership, work motivation, and compensation on the performance of employees of PT. Banyumas Family Venture Business Partner. The population is employees of the marketing department (Account Officer) with a sampling technique using random sampling. The feasibility test of the model was carried out through the F test and showed that the results of this research model were feasible. The test results show that the physical work environment, leadership, work motivation, compensation partially have a positive and significant effect on employee performance. Thus, the first, second, third and fourth hypotheses are accepted. Suggestions in this study are: the importance of a work environment that is free from noise, the need for leaders to absorb ideas from subordinates, employees need to apply a voluntary attitude to their work, educational incentives need to be given to employees who want to continue their education